Do Biologics Protect Patients With Psoriasis From Myocardial Infarction? A Retrospective Cohort. Issue 6 (November 2016) - Gulliver, Wayne P.; Randell, Shane; Gulliver, Susanne; Connors, Sean; Bachelez, Hervé; MacDonald, Don; Gladney, Neil; Morrissey, Andrea; Fleming, Patrick
Background: Psoriasis is a chronic immune-mediated inflammatory disorder that affects approximately 2% to 3% of the population, which translates to 17 million in North America and Europe and approximately 170 million people worldwide. Although psoriasis can occur at any age, most cases develop before age 40 years. Some larger studies have noted bimodal age at onset with the first peak occurring at approximately age 30 years and the second peak at around 55 to 60 years, but most patients have a younger age of onset (15-30 years). Psoriasis is associated with multiple comorbidities, decreased quality of life, and decreased longevity of life. Two recent systematic reviews and a meta-analysis concluded that psoriasis patients are at increased risk of major adverse cardiovascular events. Multiple studies confirm that many of the comorbidities found in patients with psoriasis are also important risk factors for cardiovascular disease, stroke, diabetes mellitus, hypertension, hyperlipidemia, obesity, and metabolic syndrome. Methods: We conducted a retrospective cohort study using charts from a dermatology clinic combined with an administrative database of patients with moderate to severe psoriasis in Newfoundland and Labrador, Canada. We examined the role of clinical predictors (age of onset of psoriasis, age, sex, biologic use) in predicting incident myocardial infarction (MI). Results: Logistic regression revealed that age of onset (odds ratio [OR], 8.85; P = .005), advancing age (OR, 1.07; P < .0001), and being male (OR, 3.64; P = .018) were significant risk factors for the development of MI. Neither biologic therapy nor duration of biologic therapy were statistically significant risk factors for the development of MI. Our study found that in patients with psoriasis treated with biologics, there was a nonsignificant trend in reduced MI by 78% (relative risk, 0.18; 95% confidence interval, 0.24-1.34; P = .056). Conclusion: Our study demonstrated a trend toward decreased MI in patients with moderate to severe psoriasis on biologics. Patients with an early age of onset of psoriasis (<25 years) were nearly 9 times more likely to have an MI. Clinicians should consider appropriate cardiovascular risk reduction strategies in patients with psoriasis.